2008
DOI: 10.1029/2008ja013192
|View full text |Cite
|
Sign up to set email alerts
|

Altered solar wind‐magnetosphere interaction at low Mach numbers: Coronal mass ejections

Abstract: [1] We illustrate some fundamental alterations of the solar wind-magnetosphere interaction that occur during low Mach number solar wind. We first show that low Mach number solar wind conditions are often characteristic of coronal mass ejections (CMEs) and magnetic clouds in particular. We then illustrate the pivotal role of the magnetosheath. This comes from the fact that low Mach number solar wind leads to the formation of a low thermal b magnetosheath downstream of the bow shock. This property influences mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
198
2
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(235 citation statements)
references
References 149 publications
26
198
2
1
Order By: Relevance
“…They showed that the dayside magnetopause shape in the yz plane is an oval elongated along the y direction, and the magnetotail magnetopause is an oval elongated along the z direction. Using the theoretical analysis and MHD simulations, Lavraud and Borovsky [2008] suggested that, in addition to accelerating flows tailward along the magnetopause, enhanced magnetic forces in the magnetosheath during strong IMF exert an asymmetric pressure on the magnetopause so that it may deform and get elongated in the direction of IMF. Previous work also specially investigated the situations of distant geomagnetic tail.…”
Section: 1002/2013ja019257mentioning
confidence: 99%
“…They showed that the dayside magnetopause shape in the yz plane is an oval elongated along the y direction, and the magnetotail magnetopause is an oval elongated along the z direction. Using the theoretical analysis and MHD simulations, Lavraud and Borovsky [2008] suggested that, in addition to accelerating flows tailward along the magnetopause, enhanced magnetic forces in the magnetosheath during strong IMF exert an asymmetric pressure on the magnetopause so that it may deform and get elongated in the direction of IMF. Previous work also specially investigated the situations of distant geomagnetic tail.…”
Section: 1002/2013ja019257mentioning
confidence: 99%
“…When it is low, magnetic forces dominate. This basic change leads to a dichotomy in the type of solar windmagnetosphere interaction, in many respects, as synthesized in Lavraud and Borovsky [2008] (see also Vasyliunas [2004] and Siscoe [2011] for complementary discussions to this topic).…”
Section: Introductionmentioning
confidence: 99%
“…These ingredients combine into the solar wind electric field, a prime parameter affecting the coupling at the dayside magnetosphere through magnetic reconnection, which may lead to geomagnetic storms during strong driving [e.g., Gonzalez and Mozer, 1974;Perreault and Akasofu, 1978;Kan and Lee, 1979]. Another important parameter in solar wind-magnetosphere interaction is the solar wind Alfvén Mach number M A : the ratio of the bulk solar wind to Alfvén speeds [Lavraud and Borovsky, 2008;Borovsky, 2008]. This is because M A directly controls the bow shock compression ratio and the value of the plasma b (ratio of the thermal plasma to magnetic pressures) in the downstream magnetosheath, which in turn changes which of the magnetic or thermal plasma forces dominates the dynamics in the magnetosheath [Lavraud and Borovsky, 2008;Borovsky et al, 2009;Lopez et al, 2010Lopez et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Several studies have examined the relationship between (1) enhanced CPCP and the southward interplanetary magnetic field (IMF), and (2) enhanced ring current response and the southward IMF [e.g., Gonzalez et al, 1994;Russell et al, 2001;Siscoe et al, 2002aSiscoe et al, , 2002bSiscoe et al, 2004;Merkin et al, 2005;Ridley, 2007;Kivelson and Ridley, 2008;Lavraud and Borovsky, 2008;Lopez et al, 2009;Lopez et al, 2010]. Gonzalez et al [1994] found that ring current response grows in response to prolonged periods of southward IMF in data.…”
Section: Introductionmentioning
confidence: 99%